Design of Decision Support System Determination of Indonesian Smart Card Receiver (KIP) Using Simple Additive Weighting (Saw) Method Based On Mobile Web - Anggun, Dewi Anggun; Hasbiana, Hasbiana; Selvy, Selvyani; Siska, Siska Ulandari; Indah, Indah Sari; Bunga, Bunga Intan; Andri, Andri Anto Tri Susilo (ADPEBI, 2022)
In addition, education is a very decisive instrument in contributing to the progress of a nation in building the character of the nation. Smart Indonesia Card (KIP) is a card that is given as a marker or identity of the recipient of the Smart Indonesia Program (PIP) assistance. The Smart Indonesia Card (KIP) provides assurance and certainty that school – age children are registered as recipients of educational assistance. Each child receiving PIP education assistance is only entitled to receive 1 KIP card.